2014
DOI: 10.1116/1.4901872
|View full text |Cite
|
Sign up to set email alerts
|

Study on contact distortion during high aspect ratio contact SiO2 etching

Abstract: As pattern density is increased in semiconductor integrated circuits (ICs) and pattern sizes are decreased to nanometer scale, high aspect ratio contact etching has become one of the most difficult processes in nanoscale IC fabrication. The increase in aspect ratio of the contact oxide etching raises problems such as low mask selectivity, microloading, pattern degradation, and etch stops. In this study, the authors investigated the effect of various oxide etch conditions such as mask materials, mask thickness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Feature distortion includes line (or contact) etch roughness, twisting, and producing noncircular vias. 3,9,56 The latter feature distortion is shown in Fig. 21, where horizontal sections of the feature are shown (with and without charging) at different heights in the feature.…”
Section: Charging Of Featuresmentioning
confidence: 97%
See 2 more Smart Citations
“…Feature distortion includes line (or contact) etch roughness, twisting, and producing noncircular vias. 3,9,56 The latter feature distortion is shown in Fig. 21, where horizontal sections of the feature are shown (with and without charging) at different heights in the feature.…”
Section: Charging Of Featuresmentioning
confidence: 97%
“…2,6 Maintaining CDU requires minimizing pattern distortion, in which an initially circular mask opening is not preserved through the depth of the feature, evolving into ellipses or other noncircular shapes. [7][8][9] CER originates from nonuniformities in the mask due to stochastic processes during etching or from the lithography-development process. These nonuniformities are then imprinted into the sidewalls of the feature by anisotropic delivery of activation energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of amorphous carbon as an alternative hard mask for conductive or dielectric underlayer HAR etching has been introduced as a means of addressing the limitations associated with conventional single-layer hard masks based on silicon. The utilization of an amorphous carbon layer (ACL) as an etching mask in nanoscale plasma etching patterning is facilitated by its impressive physical properties, including a high melting point, exceptional hardness, and resistance to corrosion and etching in Cl- or F-containing gases. Additionally, in both current and next-generation semiconductor processing, the ACL hard mask, in conjunction with a complex gas mixed plasma, can be leveraged to achieve high etching selectivity in HAR etching. In industrial semiconductor plasma etching, three or more complex gas mixtures, which are based on inert gases such as argon and composed of a combination of oxygen, C x F y , and C x H y F z gases, are used to control the etch profile and selectivity. , In a complex gas mixture, inert gas is injected to control the plasma density and degree of dissociation rate, and a trace amount of oxygen gas is injected to control the degree of precursors and deposited polymers produced in the plasma. , However, the high removability of the ACL by oxygen can result in unwanted sidewall etching of the ACL hard mask when exposed to a processing plasma containing oxygen gas, leading to a distorted etch profile and increased pattern opening. Thus, it is imperative to analyze and regulate the etching characteristics of the ACL when using oxygen gas as the profile of the hard mask holds a significant influence on the profile of the bottom layer to be etched, and thus greatly impacts the device quality and performance.. , …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] In the RIE process with FC gas, a suitable thickness of amorphous-CF x (a-CF x ) film deposited on the mask or sidewalls of the hole by CF x radicals plays an important role in protecting the structures from ion bombardment, leading to high selectivity and reduction of side etching. Nevertheless, it has been reported that excessive or lack of a-CF x film deposition leads to various hole profile issues, such as bowing (increased hole diameter near the middle of a hole [12][13][14] ), distortion, 15,16) and striation (vertical scratches on the sidewall 17) ). Furthermore, the conductivity of a-CF x films has also been reported, where associated features may induce charging at the bottoms of the high-AR holes during the RIE process.…”
mentioning
confidence: 99%